How physical exercise influences academic burnout among Chinese “Double Non” college students: the chain mediation role of mobile phone addiction and learning engagement - Jin, Chao; Fan, Chunhong; Niu, Jinpeng (Frontiers in Psychology, 2024)
Background: With mental anxiety caused by the COVID-19 pandemic, the trend of "lying down" has become increasingly prevalent among Chinese college students such as not thinking ahead, decadent abandonment, and being weak daily.Particularly, Chinese "Double Non" college students are more likely to face academic burnout due to lower school satisfaction and after-degree employment ratio, in comparison to "Double First-Class" college students.Objectives: In view of this, the present study examined the structural relationships of physical exercise, mobile phone addiction, learning engagement, and academic burnout among Chinese "Double Non" college students, aiming at exploring corresponding mechanism to provide supportive guidance for alleviating potential academic burnout.This study adopted a cross-sectional survey approach among the sample of "Double Non" college students in China. We recruited 930 participants (272 men and 658 women) in the second half of the 2022-2023 academic year, all of whom completed questionnaires involving Physical Exercise Rating Scale, Mobile Phone Dependence Index Scale, Utrecht Work Engagement Scale-Student, and Maslach Burnout Inventory-Student Survey. A series of statistical analyses, including 3 descriptive statistics, bivariate correlations, and direct and indirect effects among study variables, were proceeded based on the collected data.The results showed that physical exercise can not only directly and negatively influence academic burnout, but also indirectly and negatively influence academic burnout through the mediation of mobile phone addiction as well as the chain mediation of both mobile phone addiction and learning engagement. While physical exercise had no significantly indirect effect on academic burnout via learning engagement.Discussion: Physical exercise was proved to be an effective way to reduce mobile phone addiction and then enhance learning engagement, consequently leading to decreased academic burnout in Chinese "Double Non" college students. The findings were discussed in light of related research, and implications and future directions were put forward for application in potential theoretical research and educational practice.